Self-Perceived Evidence-Based Practice Competency and Associated Factors among Nurses at a County Referral Hospital in Kenya - Muthoni , Pauline; Mutai, Faith (Global Journal of Health Sciences, 2024)
Purpose: Evidence-based practice (EBP) is a crucial approach in healthcare that combines research evidence, clinical expertise, and patient preferences to guide decision-making. There is often a gap between knowledge of and implementation of EBP dependent on the nurses’ ability to acquire and apply knowledge in managing patients and decision-making. This study aimed to assess the self-perceived EBP competency and identify associated factors among nurses at a County Referral Hospital in Kenya. Methodology: A descriptive cross-sectional approach was used. A total of 75 nurses were recruited through stratified sampling. Semi-structured questionnaire was used to collect data on individual factors while validated tools were used to collect data on institutional factors and EBP competency. Data was presented in frequency tables and inferential statistics such as chi-square used to show associations. P value < 0.05 was considered significant. Results: The study showed that 52% of nurses who participated in the study had a moderate level of self-perceived EBP competency and 32% showcased a high level of competency. There was a significant association between self-perceived EBP competency and education level (p=0.04), clinical experience (p<0.001), frequency of inter-professional collaboration (p=0.009), and availability of continuing professional development (p=0.003). This study showed that most nurses at the hospital had moderate levels of EBP competency. Self-perceived EBP is significantly associated with the level of education, clinical experience, inter-professional collaboration, and availability of continuing professional development. Unique Contribution to Theory, Practice and Policy: This study applied the diffusion theory guided by Rogers' five elements. Using this theory in relation to EBP shows that the theory can be used to break down and understand nursing practice principles and factors surrounding their adoption by practitioners. This in turn can inform the restructuring of health care practices, policies formulation and intervention to enhance practice for quality care and improved health outcomes. The findings of this study can inform policy and practice development to facilitate EBP, and education for staff to equip nurses with the knowledge and tools needed to deliver high-quality, safe, and effective patient-centered care.